Facing freedom : an African American community in Virginia from Reconstruction to Jim Crow - Thorp, Daniel B. (American South series., 2017)
The history of African Americans in southern Appalachia after the Civil War has largely escaped the attention of scholars of both African Americans and the region. In this book the author relates the complex experience of an African American community in southern Appalachia as it negotiated a radically new world in the four decades following the Civil War.--Publisher's description.